These Foolish Things: On Intimacy and Insignificance in Mobile Media - Crawford, Kate (Mobile Technologies: From Telecommunications to Media, 2009)
Foundations of Mobile Media Studies gathers some of the most important texts in this emerging field, offering readers key approaches to understanding our moment and our media. The impact of mobile media is far reaching and this book discusses topics such as human intimacy, social space, political uprisings, labor, mobile phones in the developing world, gender, the mobile device’s impact on reading, mobile television, and mobile photography, among others. This carefully curated collection will serve as the central text to introduce this field to anyone eager to understand the rise of mobile technology, its impact on our relationships, and how these media have transformed the ways we understand the world around us.